Meningkatkan Kemampuan Menghafal Al-Qur’an dengan Menggunakan Metode Talaqqi Pada Anak Usia Dini di TK Islam ‘Uluwwul Himmah: Penelitian - Rosdiana; Juli Yanti Harahap; Samsul Bahri; Novita Friska (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The ability to read the Qur'an is a primary skill for Muslims. The Talaqqi method, which involves reciting verses repeatedly and then submitting them to the teacher, was chosen to facilitate memorization for young children. The research problem is how teachers implement the Talaqqi method and how to improve the ability to memorize the Qur'an in young children at the Islamic Kindergarten 'Uluwwul Himmah. The study used a classroom action research method (Action Research) with stages of planning, action, observation, and reflection in each cycle. The results of the observation showed that teachers and students interacted directly during the memorization process. Indicators of the ability to memorize short surahs according to the rules of tajweed were achieved in the categories of Good (22 children/73%) and Very Good (8 children/27%). Thus, the ability to memorize short surahs of children at the Islamic Kindergarten 'Uluwwul Himmah is quite good, fluent, and according to the rules of tajweed.